Reliability and Applications of the Numerical Wave Predictions in the Black Sea - Rusu, Eugen (Frontiers in Marine Science, 2016)
This work presents a review of the last developments in the numerical wave modelling in the basin of the Black Sea. A wave prediction system, based on the SWAN (Simulating Waves Nearshore) spectral model, has been implemented and focused on the western side of the sea. Various calibrations and validation tests have been performed considering both in situ and remotely sensed measurements. We found that the most critical factors in increasing the reliability of the wave predictions are related to the physical parameterizations of the model that should be adapted to the conditions of the enclosed seas, especially the process of whitecapping, and the accuracy and the resolution of the wind fields considered to force the wave model. Some data assimilation techniques have been also implemented for various computational levels and they were found very effective in improving the reliability of the wave predictions. Up to the present moment, some sequential methods have been applied considering several approaches as Optimal Interpolation, Linear Regression and Kalman Filter. Furthermore, some practical applications of the wave prediction system are also presented and discussed. These are related to the major storms that might be expected in the Black Sea. At this point, it has to be highlighted that an important issue when building an operational wave modeling system in such difficult environments, as the enclosed seas are, would be to implement different model configurations for different events (especially as regards the severe and extreme events). Other important issues concern the use of the wave models as a tool in the effort of preventing the sea and coastal hazards and assessing also the possible coastal impact of the marine energy farms that would operate in the nearshore. Renewable energy evaluations in the Black Sea have been also performed with this system. Finally, the results of the wave predictions were also used as input in some seakeeping studies.